Does the Hfq Protein Contribute to RNA Cargo Translocation into Bacterial Outer Membrane Vesicles? - Marisela Velez; Véronique Arluison (Pathogens)
Gram-negative bacteria release outer membrane vesicles (OMVs) that deliver various molecules, including virulence factors, to interact with their host. Recent studies have suggested that OMVs may also serve as carriers for RNAs, particularly small regulatory noncoding RNAs (sRNAs). For these RNAs to function effectively, they typically require a protein cofactor, Hfq, known as an RNA chaperone. In previous work, using molecular imaging, Circular Dichroism CD, and InfraRed FTIR spectroscopies, we demonstrated that Hfq interacts with the bacterial inner membrane and forms pores, suggesting a possible role in translocating RNA from the cytoplasm to periplasm and then to OMVs. In this study, we expand on our previous findings and provide evidence that RNA molecules bind to the Escherichia coli inner membrane in an Hfq-dependent manner. Moreover, we show that the lipid nature, in particular the presence of a cardiolipin-rich domain, is crucial for this interaction. These results reveal a new aspect of RNA translocation through the inner membrane, for further packaging in OMVs, and underscore the importance of Hfq in this mechanism.